2020
DOI: 10.1101/2020.03.08.20030643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission potential of COVID-19 in Iran

Abstract: n=50; Word limit = 50 21 We computed reproduction number of COVID-19 epidemic in Iran using two different methods. We 22 estimated R0 at 3.6 (95% CI, 3.2, 4.2) (generalized growth model) and at 3.58 (95% CI, 1.29, 8.46) 23 (estimated epidemic doubling time of 1.20 (95% CI, 1.05, 1.44) days) respectively. Immediate social 24 distancing measures are recommended. 25 26

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 11 publications
(10 reference statements)
6
31
0
Order By: Relevance
“…General characteristics of reviewed studies: We found 13 articles and 10 reports and included eight published articles / preprint manuscripts [16][17][18][19][20][21][22][23] and three reports [13,24,25]. From the 13 found articles, three articles were kept for a next version of this review [8][9][10], one article was excluded because it was not an epidemic estimation study, and one article was excluded because of absent minimum necessary details on methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…General characteristics of reviewed studies: We found 13 articles and 10 reports and included eight published articles / preprint manuscripts [16][17][18][19][20][21][22][23] and three reports [13,24,25]. From the 13 found articles, three articles were kept for a next version of this review [8][9][10], one article was excluded because it was not an epidemic estimation study, and one article was excluded because of absent minimum necessary details on methods.…”
Section: Resultsmentioning
confidence: 99%
“…Appendix Figure 1 shows the PRISMA studies ow diagram. Four of the eight reviewed articles were published (Moradi et al, Tuite et al, Zareie et al, Zhuang et al) [18,20,21,23] and the other four were in preprint phase at the time that we reviewed them (Ahmadi et al, Ghaffarzadegan et al, Muniz-Rodriguez et al, Zhan et al) [16,17,19,22]. All articles were written in English, and all reports were written in Farsi.…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, COVID-19 cases are most dramatically started to increase from the first week of March 2020. Of these, Italy is grappling with the worst outbreak, with over 35,713 confirmed cases and around 3000 deaths by March 18, 2020 [1][2][3][4][5]. This exponential increase in COVID-19 positive cases in Italy raised turmoil, and the government decree to a lockdown of the entire country [1].…”
Section: Introductionmentioning
confidence: 99%
“…Article on modeling epidemic transition of COVID-19 have been published [1][2][3][4][5][6][7][8] and based on the previous publication from China, South Korea, Iran, and Japan presented the estimation of epidemic trends and transmission rates [1][2][3][4][5][6][7][8]. Through this research, we evaluated the consistency of the containment rules and identified possible SARS-CoV-2 local mutation using the S.E.I.R mathematical model.…”
Section: Introductionmentioning
confidence: 99%
“…Although the authorities have started to confront this epidemic by shutting down the schools and universities, refusing non-local travelers in some provinces, reducing working hours for some days, implementing forms of remote work by many companies for the employees, requesting the individuals to stay at home in self-quarantine, etc., still there is a quick increase in the number of infected cases [5]. According to the literature review, there are limited published papers on Iran's status in the outbreak period of the COVID-19 [5,[14][15][16][17][18]. Therefore, given the rapid outbreak of the COVID-19 in Iran, this study was conducted in order to identify the spreading trend of this disease in Iran and all its provinces from February 19 to March 22, 2020, using the recorded data from the MHME and also to find similar provinces according to the disease spread using K-means cluster analysis (KMCA).…”
Section: Introductionmentioning
confidence: 99%